Translation of reovirus RNA species m1 can initiate at either of the first two in-frame initiation codons. - Roner, M R (1993)
The m1 species of reovirus RNA, which encodes the minor protein component mu 2, possesses two initiation codons, one "strong" according to Kozak rules and preceded by 13 residues (IC1), the other "weak" and located 49 codons downstream of the first (IC2). In reovirus-infected cells only IC2 is used, but initiation from IC1 can be activated, and efficiency of initiation from either initiation codon modulated over a wide range, by coupling unrelated sequences to either or both ends of m1 RNA. For example, when the M1 genome segment is cloned into the thymidine kinase gene of vaccinia virus in such a way that various "irrelevant" stretches of nucleotides comprising restriction endonuclease cleavage sites or promoter remnants are coupled to the 5' end of m1 RNA, translation of the resultant transcripts is also initiated at IC2, with frequencies controlled by the nature of the attached sequences. However, in rabbit reticulocyte lysates these same transcripts are translated from IC1 as well as from IC2, and transcripts in which m1 RNA is preceded by long sequences of encephalomyocarditis virus RNA (from the T7 polymerase-controlled pTM1 vector) are translated exclusively from IC1. By contrast, m1 RNA itself is translated only from IC2. It appears that the most important factor that controls the extent to which translation is initiated from IC1 and IC2 is their "availability," which is likely to be a function of the extent to which the regions on either side of them interact with each other (and also, to a lesser extent, with the 3' untranslated region) either directly or via interaction with host cell proteins. The effects described here are of considerable potential significance when genetic material is rearranged as a result of translocations, insertions, deletions, and amplifications--that is, when sequences that are normally separated are brought into apposition.